Objawy zespołu Cushinga i rzekomego przedwczesnego dojrzewania płciowego u 2-letniego dziecka z gruczolakiem nadnerczy - Boro, Hiya; Kubihal, Suraj; Dutta, Rimlee; Kubihal, Vijay; Alam, Sarah; Tandon, Nikhil (Pediatric Endocrinology Diabetes and Metabolism, 2022)
Cushing’s syndrome is a rare disease in the paediatric age group. Adrenocortical carcinomas (ACC) constitute the most common cause of Cushing’s syndrome between 1 and 5 years of age. Often, adrenocortical carcinomas co-secrete other hormones such as androgens (testosterone), deoxy-corticosterone (DOCA), or 17-hydroxy-progesterone [17(OH)P] in addition to cortisol. This may manifest with symptoms and signs of precocious puberty along with Cushing’s syndrome. It is rare for a benign adrenocortical adenoma to co-secrete androgens and other hormones in addition to cortisol. Differentiation between adenoma and carcinoma is difficult in all aspects: clinical, radiological, and histopathological. Here, we describe the case of a 2.5-year-old male child who presented with Cushing’s syndrome and virilization. Although we suspected ACC clinically, the radiological and histopathological findings were suggestive of benign adrenocortical adenoma. Our case represents the diagnostic challenge that exists in paediatric adrenocortical tumours.